Alpha-fetoprotein (AFP) in granulomatous inflammation of the mouse. - Trojan, J. (1989)
Inflammatory granulomas constituted of various proportions of macrophages, polynuclear (PMNs) and mononuclear cells were induced in adult pathogen-free mice by injecting polyacrylamide beads into subcutaneous pouches. Using specific anti-mouse alpha-fetoprotein (AFP) antibodies, the presence of AFP was immunocytochemically demonstrated in the cytoplasm of macrophages and of immature PMNs (mature PMNs and mononuclear cells were AFP negative). AFP-labelling started as soon as 36 h after granuloma induction and reached a maximum 60-72 h later, to disappear on day 5. The examination of different organs in these mice also showed a transitory labelling for AFP of liver hepatocytes and of elements of kidney and of exocrine pancreas. Parallel to these findings, the selective concentration inside the granulomatous pouches of radiolabelled AFP injected in the course of inflammation was observed. These results suggest that (a) shortly after the inflammatory reaction the synthesis of AFP is resumed by the liver; (b) the newly synthesized AFP is secreted in the serum and preferentially taken up by the granulomas; and (c) consequently, in adult mice, AFP behaves as a positive acute phase reactant. The physiopathological implications of these facts are discussed in relation with the biological properties of AFP.